Timing of liver transplantation for pediatric acute liver failure due to mushroom poisoning: a case report and literature review - Chun-Feng Yang; Chu-Qiao Sheng; Yu Ao; Yu-Mei Li (BMC, 2020)
Abstract Background Pediatric acute liver failure is a rare, life-threatening illness. Mushroom poisoning is a rare etiology. For patients with irreversible pediatric acute liver failure, liver transplantation is the ultimate lifesaving therapy. However, it is difficult to determine the optimal timing of transplantation. Here, we present a case of pediatric acute liver failure due to mushroom poisoning in northeastern China. He was treated with liver transplantation and recovered. To our knowledge, there are few reports about liver transplantation for pediatric acute liver failure caused by mushroom poisoning in mainland China. Case presentation The patient was a previously healthy 9-year-old boy who gradually developed nausea, vomiting, jaundice and coma within 5 days after ingesting mushrooms. He was diagnosed with mushroom poisoning and acute liver failure. He was treated with conservative care but still deteriorated. On the 7th day after poisoning, he underwent LT due to grade IV hepatic encephalopathy. Twenty days later, he recovered and was discharged. A review of the literature revealed that the specific criteria and optimal timing of transplantation remain to be determined. Conclusions Patients with pediatric acute liver failure should be transferred to a center with a transplant unit early. Once conservative treatment fails, liver transplantation should be performed.